Invasion of the intestinal tract by sporozoites of Eimeria coecicola and Eimeria intestinalis in naive and immune rabbits - Pakandl, Michal; Sewald, Brigitte; Drouet-Viard, Françoise (Parasitology research, 2006)
Naive and immune specific-pathogen-free rabbits were inoculated in the duodenum with sporocysts of Eimeria coecicola or Eimeria intestinalis. Samples were taken from the following tissues: duodenum (site of penetration of sporozoites), ileum (specific target site of the endogenous development of E. intestinalis), vermiform appendix (target site of E. coecicola) and two extraintestinal sites, mesenteric lymph nodes (MLNs), and spleen. The presence of sporozoites was checked by immunohistochemistry. In rabbits primary-infected with E. coecicola, large numbers of sporozoites were detected in the duodenum, extraintestinal sites, and vermiform appendix. The abundance of sporozoites in the spleen, MLN, and appendix was significantly reduced in the immune rabbits, and the migration seemed impeded. In the rabbits infected with E. intestinalis, sporozoites were absent in the spleen and MLN, indicating that the route of migration is different from that of E. coecicola. The number of sporozoites in the crypts of the ileum was markedly reduced in the immune animals.
Keywords: Intestinal Diseases, Parasitic; antigeny protozoální; interakce hostitele a parazita; Rabbits; Animals; Lymph Nodes; organismy bez specifických patogenů; sporozoiti; Antibodies, Protozoan; Peyerovy pláty; Coccidiosis; slezina; Eimeria; parazitární nemoci střev; Spleen; Intestine, Small; kokcidióza; protilátky protozoální; Host-Parasite Interactions; Antigens, Protozoan; Sporozoites; zvířata; tenké střevo; Specific Pathogen-Free Organisms; Peyer's Patches; králíci; lymfatické uzliny